A Paper‐Based Triboelectric Touch Interface: Toward Fully Green and Recyclable Internet of Things. Issue 1 (25th November 2022) - Edberg, Jesper; Boda, Ulrika; Mulla, Mohammad Yusuf; Brooke, Robert; Pantzare, Sandra; Strandberg, Jan; Fall, Andreas; Economou, Konstantin; Beni, Valerio; Armgarth, Astrid
Abstract: The transition to a sustainable society is driving the development of green electronic solutions designed to have a minimal environmental impact. One promising route to achieve this goal is to construct electronics from biobased materials like cellulose, which is carbon neutral, non‐toxic, and recyclable. This is especially true for internet‐of‐things devices, which are rapidly growing in number and are becoming embedded in every aspect of our lives. Here, paper‐based sensor circuits are demonstrated, which use triboelectric pressure sensors to help elderly people communicate with the digital world using an interface in the form of an electronic "book", which is more intuitive to them. The sensors are manufactured by screen printing onto flexible paper substrates, using in‐house developed cellulose‐based inks with non‐hazardous solvents. The triboelectric sensor signal, generated by the contact between a finger and chemically modified cellulose, can reach several volts, which can be registered by a portable microcontroller card and transmitted by Bluetooth to any device with an internet connection. Apart from the microcontroller (which can be easily removed), the whole system can be recycled at the end of life. Abstract : A triboelectric touch interface, manufactured using printed electronics on flexible paper substrates, using cellulose‐based functional inks is demonstrated. These metal‐free green electronics circuits are implemented in an "electronic book" demonstrator, equipped with wireless communication that can control remote devices, as a step toward sustainable and recyclable internet‐of‐things devices.